Komunikacja marketingowa banków Unii Europejskiej z klientami detalicznymi : na przykładzie private banking - Bednarska-Olejniczak, Dorota (Marketing Communication of EU Banks With Retail Clients : on the Example of Private Banking, 2008)
Private banking is a particular area of retail banking. Its distinctiveness results from high profit generation, fast tempo of wealth accumulation in modem society and specific needs of this demanding target market. Due to the above, private banking requires special solutions in regard to marketing communication, since application of standard retail banking activities is pointless. The solutions need to match particular features and requirements of the target market. Target market of private banking is not homogeneous - it consists of multiple sub-segments with different needs. The aim of this paper is to present the reasons for such differentiation, with particular attention to cultural and historical determinants. The paper focuses on presentation and characteristics of individual segments of private banking for High Net Worth customers in selected EU countries, as well as demonstration of matching marketing communication solutions, accounting for cultural differences. Specificity of Polish market is also presented. Preparation and implementation of efficient promotional instruments by domestic banks that target wealthy clientele should be based on carefui segmentation of the market, with distinct instruments matching the needs of mass affluent (target market for personal banking, and those of the Polish HNWI segment. Considering global character of private banking services, Polish banks should draw on the experience of Western banks (e.g. in regard to customer service standards), while paying attention to specificity and economic/cultural distinctness of Polish market. The paper discusses also the role of personal service (personal financial advisors) in promotional activities of private banking.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 71-80